2016
DOI: 10.1038/leu.2016.213
|View full text |Cite
|
Sign up to set email alerts
|

Survival control of malignant lymphocytes by anti-apoptotic MCL-1

Abstract: Programmed apoptotic cell death is critical to maintain tissue homeostasis and cellular integrity in the lymphatic system. Accordingly, the evasion of apoptosis is a critical milestone for the transformation of lymphocytes on their way to becoming overt lymphomas. The anti-apoptotic BCL-2 family proteins are pivotal regulators of the mitochondrial apoptotic pathway and genetic aberrations in these genes are associated with lymphomagenesis and chemotherapeutic resistance. Pharmacological targeting of BCL-2 is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 100 publications
1
45
0
Order By: Relevance
“…In chronic infection, Mcl-1 is downregulated in CD127 low antigen specific CTLs along with up-regulation of Bim and this causes apoptosis of CD8 + T cells (272) or hyporeactivity of CTLs, which could possibly be treated by apoptosis inhibition or IL-7 treatment (273). Conversely, Mcl-1 enhances survival in a variety of cancers including T cell lymphomas and various Mcl-1 inhibitors are being explored (274). Given the robust loss of cells anytime Mcl-1 is deleted, there are some substantial concerns about the potential cytotoxicity of Mcl-1 inhibitors.…”
Section: Bcl-2 Family Membersmentioning
confidence: 99%
“…In chronic infection, Mcl-1 is downregulated in CD127 low antigen specific CTLs along with up-regulation of Bim and this causes apoptosis of CD8 + T cells (272) or hyporeactivity of CTLs, which could possibly be treated by apoptosis inhibition or IL-7 treatment (273). Conversely, Mcl-1 enhances survival in a variety of cancers including T cell lymphomas and various Mcl-1 inhibitors are being explored (274). Given the robust loss of cells anytime Mcl-1 is deleted, there are some substantial concerns about the potential cytotoxicity of Mcl-1 inhibitors.…”
Section: Bcl-2 Family Membersmentioning
confidence: 99%
“…Mcl-1 degradation is regulated by its phosphorylation at several sites, leading to subsequent ubiquitination by E3 ligases such as F-box and WD repeat domain-containing 7 (FBW7), Mule, and β-TrCP (69). Mcl-1 depletion clearly contributes to apoptosis in hematopoietic cells (10,11). However, the role of Mcl-1 degradation in solid tumor cells is unclear, as Mcl-1 depletion typically occurs prior to the onset of apoptosis in response to therapeutic treatment, and by itself, is insufficient to trigger cell death (12).…”
Section: Introductionmentioning
confidence: 99%
“…3b). Given that GSK-3 is known to regulate stability of the Bcl-2 family survival protein Mcl-1 [31][32][33][34] we performed immunoblot analysis on sorted DP thymocytes for Mcl-1 protein levels. LckCre + GSK-3αβ fl/fl DP thymocytes exhibited significantly higher levels of Mcl-1, consistent with enhanced DP cell survival ( Fig.…”
Section: Lckcrementioning
confidence: 99%
“…While it has been reported that constitutive activation of Akt in absence of pre-TCR and NOTCH signals can prevent programmed cell death of DN thymocytes independent of several Bcl-2 members there is evidence that Bcl-2 family members such as Mcl-1 play a crucial role in T cell survival, development and tumorigenesis [30][31][32][33][34][35] . GSK-3 regulates Mcl-1 stability through ubiquitin-mediated degradation 34,35 .…”
Section: Introductionmentioning
confidence: 99%